Recycled Glass Bottles for Craft-Beer Packaging: How to Make Them Sustainable? An Environmental Impact Assessment from the Combined Accounting of Cullet Content and Transport Distance - Magdalena Wojnarowska; Magdalena Muradin; Annarita Paiano; Carlo Ingrao (Resources)
Effective waste management plays a vital role in advancing sustainability goals across industries, with particular relevance to glass manufacturing—a sector that generates significant environmental challenges due to its resource-intensive production processes and high waste generation. The scale of production results in the accumulation of substantial amounts of waste glass, which, if not efficiently managed, contributes to environmental degradation. In this context, craft-beer production, which increasingly relies on glass bottles for packaging, presents unique challenges and opportunities for implementing sustainable practices. The sector faces trade-offs between increasing the use of recycled glass (cullet) and addressing the environmental impacts associated with transporting materials over long distances. The combination of centralized waste processing systems and long-distance transport adds economic and environmental costs, with transportation contributing up to 60–80% of overall waste management expenses. Addressing these issues requires an integrated approach that evaluates critical variables, such as cullet content and transport logistics, to identify solutions that balance economic and environmental efficiency. This study addresses the pressing issue of optimizing the recycling of glass bottles for craft-beer packaging by examining the combined influence of cullet content and transport distance on environmental sustainability. The objective was to assess the environmental impacts associated with varying levels of cullet content (0%, 57%, and 90%) and transport distances (25 to 250 km) using life cycle assessment (LCA) methodology aligned with ISO standards and the Product Environmental Footprint Category Rules (PEFCRs). The analysis demonstrated that increasing the proportion of recycled glass and reducing transport distances are key to improving environmental efficiency in bottle production. The most environmentally favorable scenario, S03 (90% cullet content), remains effective even at greater transport distances. In contrast, scenario S02 (57% cullet content) requires further distance reductions to maintain efficiency, particularly beyond 150 km. These findings highlight the importance of shorter supply chains and higher recycled material content as essential steps toward sustainable glass bottle production for the craft-beer industry.